Epidermal Growth Factor Induces Vasoconstriction Through the Phosphatidylinositol 3-Kinase-Mediated Mitogen-Activated Protein Kinase Pathway in Hypertensive Rats - Kim Junghwan; Lee Chang-Kwon; Park Hyo-Jun; Kim Hyo Jin; So Hyun Ha; Lee Keun Sang; Lee Hwan Myung; Roh Hui Yul; Choi Wahn Soo; Park Tae Kyu; Kim Bokyung (Elsevier, 2006)
Abstract.: We investigated whether increased contractile responsiveness to epidermal growth factor (EGF) is associated with altered activation of mitogen-activated protein kinase (MAPK) in the aortic smooth muscle of deoxycorticosterone acetate (DOCA)-salt hypertensive rats. EGF induced contraction and MAPK activity in aortic smooth muscle strips, which were significantly increased in tissues from the DOCA-salt hypertensive rats compared with those from sham-operated rats. AG1478, PD98059, and LY294002, inhibitors of EGF receptor (EGFR) tyrosine kinase, MAPK/extracellular signal-regulated kinase (ERK) kinase, and phosphatidylinositol 3-kinase (PI3K), respectively, inhibited the contraction and the activity of ERK1/2 that were elevated by EGF. Y27632 and GF109203X, inhibitors of Rho kinase and protein kinase C, respectively, attenuated EGF-induced contraction, with no diminution of ERK1/2 activity. Although EGF also elevated the activity of EGFR tyrosine kinase in both sham-operated and DOCA-salt hypertensive rats, the expression and the magnitude of activation did not differ between strips. These results strongly suggest that EGF induces contraction by the activation of ERK1/2, which is regulated by the PI3K pathway in the aortic smooth muscle of DOCA-salt hypertensive rats. Keywords:: epidermal growth factor, hypertension, vasoconstriction, mitogen-activated protein kinase, phosphatidylinositol 3-kinase